Open Muscle-Preserving Pedicle Screws Fixation Versus Conventional Open Posterior Approach in Thoracolumbar Burst Fracture without Neurologic Injury - Piyapromdee, MD, Urawit; Budsayavilaimas, MD, Chanthong; Choovongkomol, MD, Kongtush; Tanaviriyachai, MD, Terdpong; Sudprasert, MD, Weera (Journal of Southeast Asian Orthopaedics, 2022)
Introduction: Patients who sustained thoracolumbar spine fracture without neurological deficit often require surgical treatment. The conventional open posterior approach had some disadvantages including post-operative pain, blood loss, and duration of the operation. The minimally invasive approach, open muscle-preserving pedicle screw fixation, was proposed to have more benefit than the conventional approach. This study evaluated the clinical and perioperative outcomes of thoracolumbar burst fracture fixation using the open muscle-preserving approach and the conventional open posterior approach. Methods: A prospective cohort study from June 2016 to June 2017 of the open muscle-preserving pedicle screw fixation approach was done compared to the historical control of the conventional open posterior approach from May 2015 to May 2016. The post-operative pain score, blood loss, duration of operation and clinical outcome were analyzed. Results: Twenty-three patients were enrolled in the muscle-preserving approach group, and 27 patients treated with the conventional open posterior approach were the control group. Post-operative VAS was significantly better in the muscle-preserving group (P<0.001). The mean operating time was significantly shorter in the muscle-preserving group (60.4±17.3 min. vs. 90.9±18.9 min., p<0.001). Moreover, the mean intra-operative blood loss of the muscle-preserving group was also significantly lower (156.96±96.3ml. vs. 269.26±147.6ml., p=0.003). Conclusion: Our study results indicate a superiority of the open muscle-preserving approach over the conventional open posterior approach for a thoracolumbar burst fracture without neurologic injury in terms of post-operative pain score, blood loss and duration of operation. The open muscle-preserving approach is an alternative treatment for thoracolumbar burst fractures.